From tourism and disability to accessible tourism: a perspective article. Issue 1 (8th February 2020) - Darcy, Simon; McKercher, Bob; Schweinsberg, Stephen
Abstract : Purpose: This paper aims to examine the development of disability and tourism to the conceptualising and defining of accessible tourism. Design/methodology/approach: This paper uses a limited review of the literature as its main approach. Findings: In reviewing the development of the field from disability and tourism to accessible tourism, it became apparent that there has been a change in focus on the accessibility of the key sectors of tourism (e.g. transport, accommodation and attractions) to incorporating an embodied understanding of tourism in developing accessible destination experiences that provide an equality of offering to that of nondisabled tourists. Originality/value: This paper makes a contribution by clearly following the development of the field from papers that only considered tourism and disability to conceptualise and define the accessible tourism field. It then goes on to identify a significant challenge due to an underlying empirical data gap through a lack of nationally and regionally collected tourism data that incorporates disability questions.